Application of Six Sigma Method for Quality Control of Palm Kernel Oil Production In PT Socfin Indonesia - Novita Sari; Mardiningsih (Journal of Mathematics Technology and Education, 2021)
Socfin Indonesia is an upstream plantation company with the main products are Crude Palm Oil (CPO), Palm Kernel Oil (PKO), and Karet Alam. The problems that encounter is still found a defective product where the quality of the products produced still not fulfilling the company's quality standards. The purpose of this study was to apply the Six Sigma method in quality control for reducing defects in palm kernel oil (PKO) production at PT. Socfin Indonesia. The company has the characteristics for quality of palm kernel oil (PKO) products that consist of water content, broken core levels and dirt content. Based on the data obtained, the percentage of disability was 31.73% while the company's tolerance limit was 30% for overall production. The method used was Six Sigma with the DMAIC procedure. Based on the results of the study, the company's DPMO value was 105,724 with a company sigma capability value of 2.7496. The ability to produce defective products was about 31.72%. The proposed for improving the quality product of palm kernel oil (PKO) with the Six Sigma method against the company by complying the Standard Operation Procedure (SOP) that has been made to avoid anythings that can interfere the production process.